2008
DOI: 10.1590/s0100-54052008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de métodos para a detecção de Fusarium graminearum em sementes de trigo (Triticum aestivum L.)

Abstract: O objetivo deste trabalho foi comparar diferentes métodos utilizados para a detecção de Fusarium graminearum em sementes de trigo. Foram empregados 22 tratamentos: papel de filtro (PFC) com congelamento; papel de filtro (PF); PF mais 0,02% de 2,4 - D; meio semi-seletivo (MSS); MSS mais 0,02% de 2,4 - D; MSS mais KCl (-0,8 MPa); KCl, NaCl, manitol e sacarose nos potenciais osmóticos de -0,4, -0,6, -0,8 e -1,0 MPa. O delineamento estatístico empregado foi o inteiramente casualizado, com quatro repetições (duas p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
1
1
Order By: Relevance
“…Therefore, BTF presented a lower sensibility to detect F. graminearum compared to PDA medium. These results differed from that obtained by Garcia Júnior et al (2008), in which no significant differences were observed on F. graminearum incidence between semi-selective mediums and BTF. The results obtained in the study showed that is not always possible to safely detect all fungi in wheat seeds by the same method.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, BTF presented a lower sensibility to detect F. graminearum compared to PDA medium. These results differed from that obtained by Garcia Júnior et al (2008), in which no significant differences were observed on F. graminearum incidence between semi-selective mediums and BTF. The results obtained in the study showed that is not always possible to safely detect all fungi in wheat seeds by the same method.…”
Section: Resultscontrasting
confidence: 99%
“…Through seeds, microorganisms can be transported for long distances and easily introduced into new areas (Nasser, 1987). The incidence of F. graminearum on seeds was quantified in many studies (Telles Neto et al, 2007;Kabeere et al, 1997;Garcia Júnior et al, 2008;Kobayasti and Pires, 2011) and could be up to 48% (Kabeere et al, 1997;Danelli et al, 2012). For P. grisea, the pathogen incidence was also measured in different studies, and most of them reported incidences about 6 to 18% (Goulart and Paiva, 1991;Goulart and Paiva, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…2008. Além disto, Garcia Júnior et al (2008) relataram que a detecção de F. graminearum pode ser prejudicada pela alta incidência de fungos saprofíticos, como Cladosporium sp.…”
Section: Resultsunclassified
“…Water stress is used to control or inhibit seed germination under different circumstances such as in health tests on paper substrate (CELANO et al, 2012) and potato dextrose agar medium (PDA) (GARCIA JÚNIOR et al, 2008), and in fungal inoculation tests (FARIAS et al, 2010), besides simulating water deficit (GIROTTO et al, 2012), osmotic and matric conditioning (QUEIROGA et al, 2011) for crops of interest. A water restriction condition can be obtained by adjusting water potential with osmotically active solutes, with the most common being mannitol, polyethylene glycol, maltose (GIROTTO et al, 2012), KCl, NaCl, sucrose (GARCIA JÚNIOR et al, 2008), or CaCl 2 (MACHADO NETO et al, 2006).…”
Section: Introductionmentioning
confidence: 99%